Janus Microdimer Surface Walkers Propelled by Oscillating Magnetic Fields. (15th January 2018) - Li, Tianlong; Zhang, Anning; Shao, Guangbin; Wei, Mengshi; Guo, Bin; Zhang, Guangyu; Li, Longqiu; Wang, Wei
Abstract: Recent strides in micro‐ and nanofabrication technologies have enabled researchers to design and develop micro‐ and nanoscale robotic systems with enhanced power, functionality, and versatility. Because of their capability of remote actuation and navigation, synthetic micro‐ and nanomotors powered by oscillating magnetic fields have recently gained considerable attention. In this article, a new type of magnetic surface walker that can achieve speeds of up to 18.6 µm s −1 (≈4 body length s −1 ) in an oscillating magnetic field operated at 25 Hz and ≈2.7 mT is reported. Two magnetic Janus microspheres spontaneously form a microdimer via magnetic dipolar interactions, and this microdimer rolls its two "feet" back and forth in an alternating fashion. In addition to propulsion, the oscillating magnetic field can also precisely steer these surface walkers through complicated structures, and an extensive discussion of their performance in various experimental conditions is provided. The reported propulsion mechanism opens new possibilities for the design of remotely actuated microrobots for a wide range of applications. Abstract : Magnetically coated Janus microspheres align and bind into dimers in an oscillating magnetic field, and leap into directional motion by alternating their two spheres back and forth in an asymmetric fashion dictated by the underlying substrate. The speed and directionality of these surface microwalkers can be precisely manipulated, and they circumvent and overcome obstacles, demonstrating their potential usefulness.